Elizabeth blue [videorecording (DVD)] - Sabella, Vincent; Schafer, Anna; Vincent, Ryan; Akinnuoye-Agbaje, Adewale, 1967- (Global Digital Releasing, 2018)
Recently released from a psychiatric hospital, Elizabeth returns to her L.A. apartment where she lives with her fiance. With the guidance of her new psychiatrist, she works at regaining control of her mental stability as she begins to plan her wedding. Navigating hallucinations, medications, and her unsupportive mother, she clings to the hope that love will truly conquer all, even mental illness.